2010
DOI: 10.1038/cgt.2010.4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of metastatic neuroblastoma with systemic oncolytic virotherapy delivered by autologous mesenchymal stem cells: an exploratory study

Abstract: Treatment of metastatic tumors with engineered adenoviruses that replicate selectively in tumor cells is a new therapeutic approach in cancer. Systemic administration of these oncolytic adenoviruses lack metastatic targeting ability. The tumor stroma engrafting property of intravenously injected mesenchymal stem cells (MSCs) may allow the use of MSCs as cellular vehicles for targeted delivery. In this work, we study the safety and the efficacy of infusing autologous MSCs infected with ICOVIR-5, a new oncolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 33 publications
5
94
0
Order By: Relevance
“…The treatment was found to be safe and at 3 months, a bone marrow biopsy indicated a minimal number of tumor cells in a mostly healthy marrow (Pesonen et al, 2010). In the other study, four children with metastatic neuroblastoma refractory to first-line therapies received several doses of autologous mesenchymal stem cells loaded with oncolytic adenovirus (Garcia-Castro et al, 2010). The adenovirus used in this case was an Ad5 virus with an RGD peptide in the fiber knob, which binds to cellular integrin, and it had the 24-bp deleted (D24) E1A gene driven by the E2F-1 promoter.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The treatment was found to be safe and at 3 months, a bone marrow biopsy indicated a minimal number of tumor cells in a mostly healthy marrow (Pesonen et al, 2010). In the other study, four children with metastatic neuroblastoma refractory to first-line therapies received several doses of autologous mesenchymal stem cells loaded with oncolytic adenovirus (Garcia-Castro et al, 2010). The adenovirus used in this case was an Ad5 virus with an RGD peptide in the fiber knob, which binds to cellular integrin, and it had the 24-bp deleted (D24) E1A gene driven by the E2F-1 promoter.…”
Section: Discussionmentioning
confidence: 96%
“…Oncolytic adenoviruses have already been clinically used at two centers for the treatment of children with metastatic neuroblastoma (Garcia-Castro et al, 2010;Pesonen et al, 2010). In one study, a 6-year-old boy with lymph node and bone marrow metastases was treated by injection of Ad5/3-Cox2LD24 oncolytic adenovirus, which is an Ad5 virus with Ad3 fiber knob and a 24-bp deleted (D24) E1A gene driven by the cyclooxygenase-2 (COX2) promoter.…”
Section: Discussionmentioning
confidence: 99%
“…In short duration from now for active immunity against tumor will be introduced by modifying the use of MSCs and NSCs whose aim is the establishment of the safety and efficacy of MSCs that expresses IL-12 (GX-051) and the route of administration of these drugs are intra-tumorally in patients suffering from head and neck cancer. Garcia-Castro and their co-workers demonstrated that using auto-logous MSCs laden with oncolytic adenovirus (ICOVIR-5) in a sample of four children shows efficacy and safety with metastatic neuroblastoma in several doses via infusion administration [223]. A single case was documented about the reduction of disease in a child after three years of therapy.…”
Section: Doorway Of Therapeutic Stem Cells In Clinical Trialsmentioning
confidence: 99%
“…MSCs were recruited and migrated into the tumor. In one of the young patients, the virus destroyed enough tumor cells to generate a CD8 cytotoxic response, the tumor disappeared and the patient was free of the disease (Garcia-Castro et al 2010). Improving oncolytic viruses and adjusting the doses of injected MSCs could therefore have potential as be an alternative therapy in some advanced cancers in the future.…”
Section: Clinical Trials Using Cell Therapymentioning
confidence: 99%